2021
DOI: 10.1186/s12870-021-03243-8
|View full text |Cite
|
Sign up to set email alerts
|

SWATH-MS based quantitive proteomics reveal regulatory metabolism and networks of androdioecy breeding system in Osmanthus fragrans

Abstract: Background The fragrant flower plant Osmanthus fragrans has an extremely rare androdioecious breeding system displaying the occurrence of males and hermaphrodites in a single population, which occupies a crucial intermediate stage in the evolutionary transition between hermaphroditism and dioecy. However, the molecular mechanism of androdioecy plant is very limited and still largely unknown. Results Here, we used SWATH-MS-based quantitative approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 65 publications
(59 reference statements)
0
1
0
Order By: Relevance
“…We previously attempted to study the breeding system of O. fragrans from the perspective of sequential windowed acquisition of all theoretical mass spectra (SWATH-MS) quantitative proteomics, and the results showed that differentially expressed proteins in glucose metabolism, secondary metabolism and calcium signaling pathways may affect the sex differentiation [ 31 ]. As is known to all, important information about regulating gene function is hidden in these miRNAs, and the study of miRNAs in the genus Osmanthus and even the Oleaceae has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…We previously attempted to study the breeding system of O. fragrans from the perspective of sequential windowed acquisition of all theoretical mass spectra (SWATH-MS) quantitative proteomics, and the results showed that differentially expressed proteins in glucose metabolism, secondary metabolism and calcium signaling pathways may affect the sex differentiation [ 31 ]. As is known to all, important information about regulating gene function is hidden in these miRNAs, and the study of miRNAs in the genus Osmanthus and even the Oleaceae has not been reported.…”
Section: Introductionmentioning
confidence: 99%